SARS-CoV-2 Spreads Globally Through the Object-to-Human Transmission of Cross-Border Logistics - Shao, Wenxia; Ye, Qing (Frontiers in Microbiology, 2022)
With globalization, the demand for transnational logistics is growing rapidly. However, the object-to-human transmission of SARS-CoV-2 has been reported in transnational logistics production, transportation, storage, sales, and consumption. Every link of transnational logistics has the risk of spreading the COVID-19 pandemic. It is concluded that low temperatures, dry environments, and smooth surfaces are conducive to the long-term survival of SARS-CoV-2 on the surface of transnational goods. Epidemiological investigation and big data analysis show that the object-to-human transmission route of direct contact with contaminated cold chain goods plays a key role in the outbreak and transmission of the COVID-19 pandemic. This may be the most crucial reason for the global spread of SARS-CoV-2 caused by transnational logistics. It is an effective way to prevent the spread of SARS-CoV-2 from object-to-human through transnational logistics by strengthening the management of employees in all aspects of transnational logistics, carrying out comprehensive disinfection and quarantine of and guiding consumers to handle transnational goods properly.